2020
DOI: 10.1016/j.jse.2020.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical effects of superior capsular reconstruction in a rotator cuff–deficient shoulder: a cadaveric study

Abstract: Background: Superior capsular reconstruction (SCR) has been gaining popularity as a treatment for irreparable rotator cuff tears (RCTs), especially in younger patients. This biomechanical study aimed to investigate how SCR affects functional abduction force, humeral head migration, and passive range of motion following an irreparable RCT. We hypothesized that SCR will restore these parameters to nearly intact shoulder levels. Methods: Six fresh-frozen cadaveric shoulders were evaluated using a custom biomechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 32 publications
(104 reference statements)
0
8
0
Order By: Relevance
“…The unbalanced loading condition was achieved by removing the loads from latissimus dorsi and pectoralis major, and added an additional 40N to the deltoid. Two studies reduced deltoid load by half (balanced system: 20N; unbalanced system: 40N) ( 49 , 52 ). The loading conditions were not properly displayed in the other six experiments ( 46 48 , 51 , 53 , 56 ).…”
Section: Resultsmentioning
confidence: 99%
“…The unbalanced loading condition was achieved by removing the loads from latissimus dorsi and pectoralis major, and added an additional 40N to the deltoid. Two studies reduced deltoid load by half (balanced system: 20N; unbalanced system: 40N) ( 49 , 52 ). The loading conditions were not properly displayed in the other six experiments ( 46 48 , 51 , 53 , 56 ).…”
Section: Resultsmentioning
confidence: 99%
“…14,20 Although biomechanical studies have not assessed the effectiveness of SCR with xenograft, cadaveric studies evaluating SCR with dermal allograft have shown excellent results. 55 SCR with xenograft may be able to provide similar restoration of shoulder function with more cost-effectiveness. However, use of the LHBT may be limited by its availability owing to anatomic variation or concomitant rupture.…”
Section: Discussionmentioning
confidence: 99%
“…Ishihara et al described in a cadaveric study that massive cuff tears result in not only superior instability but also anterior–posterior capsular instability ( 16 ). A recent cadaveric study by Rybalko et al found that superior capsular reconstruction (SCR) significantly decreased superior migration by 72 and 64% at 0° and 30° of abduction, respectively, compared with a full-thickness tear, largely re-centring the humeral head ( 17 ). The graft effectively functions as a spacer by shifting the humerus inferiorly and decreasing subacromial pressure.…”
Section: Operative Repairmentioning
confidence: 99%